Small Fiber Neuropathy Following Vaccination. Issue 1 (September 2016) - Kafaie, Jafar; Kim, Minsoo; Krause, Erik
Abstract: Objective: To identify clinical and quantitative relationship between vaccinations and small fiber neuropathy (SFN). SFN refers to damaged unmyelinated or thinly myelinated sensory and/or autonomic fibers. Diagnosis is primarily based on clinical presentation. Intraepidermal nerve fiber density can provide diagnostic confirmation with a sensitivity of 88% and a specificity of 91%. However, the possible association between vaccination and small fiber polyneuropathy is not well defined. Methods: Case study. Results: Fourteen-year-old white adolescent girl presented with intractable generalized pain for 1.5 years. Burning dysesthetic pain began in the lower back and progressed to all extremities 9 days following human papillomavirus vaccination. The pain persisted despite various pain medications. Examination was significant for allodynia of right scapula (T4–T6) and decreased pinprick sensation in feet. MRI Brain with and without contrast, MR Face, Orbit with and without contrast, and MR Cervical, Lumbar spines with and without contrast were all normal. Nerve Conduction Studies/Electromyogram studies were unremarkable, and skin biopsy of the right thigh and foot showed low intraepidermal nerve fiber density with normal sweat gland nerve fiber density. Conclusions: This case report describes an acute onset of non–length-dependent SFN potentially related to human papillomavirus vaccine administration. Literature review includes several similar case studies, and various pathological processes have been proposed for vaccine-associated polyneuropathies. Some theories describe immune-mediated hypersensitivity to the solvents/adjuvants and/or invasion of nervous system through a prolonged, less virulent infection. However, the lack requires that evidence must be carefully reviewed.